Pengaruh Pemangkasan Cabang dan Mikoriza terhadap Produksi dan Mutu Benih Mentimun (Cucumis Sativus L.) - APRILIANA, ANWI; PUDJIHARTATI, ENDANG; SUKIMAN, HARMASTINI (Agrotrop : Journal on Agriculture Science; Vol 9 No 1 (2019), 2019)
The Effect of Branch Pruning and Mycorrhiza o n Production and Seed Quality of Cucumis s ativus L . The purpose of this study was to obtain the best branch pruning, with or without mycorrhiza application, in order to increase the production and quality of cucumber seeds. Pruning the branch at the beginning of cucumber growth is expected to delay fruit formation and support good vegetative growth. This research was carried out in the PT. Primasid Andalan Utama seed production area in Kalibeji Village, Tuntang District, Semarang Regency, Seed Technology Laboratory and Plant Physiology Laboratory, Faculty of Agriculture and Business, Satya Wacana Christian University. This study was conducted by the split-plot randomized complete block design with 2 factors. The main plot consists of 2 levels, namely control/without mycorrhiza (M 0 ) and mycorrhiza application (M 1 ). Pruning the branches as the subplots consist of 4 levels, were pruning to the second, third, fourth and fifth branches of the cucumber plant (P 1 , P 2 , P 3 and P 4 ). DMRT was used to differentiate the significance of the treatment. The results showed that mycorrhiza application increased the percentage of root infections. The pruning to the fifth branch (P 4 ) is the best; in control without mycorrhiza (M 0 P 4 ) increased for the number of fruits, the seed weight per plant, and the germination simultaneously; whereas in mycorrhiza application (M 1 P 4 ) increased the number of fruits and the seed weight per plant.  It is also observed that the pruning to the second branch (P 1 ) increased the weight of 1000 grains, the speed of germination and the simultaneous of germination; both with and without mycorrhiza application.